A Model for Characterizing Organizational Culture in Public Educational Institutions in Colombia and Cuba (2023)
The objectiveof this paper is to develop a model to characterize the organizational culture of the Antonio José Camacho University Institution of Colombia and the Branch Entity ofCuba. The following logical thought processes were used: analysis, synthesis and induction-deduction, which allowed processing, systematizing, and interpreting the information related to the post-pandemic impact of COVID-19 on the organizational culture of university institutions such as the “Antonio José Camacho” University and the Branch Entity. The university institutions are called to maintain the educational level achieved, to have innovative thinking with a lot of creativity and a culture of detail. The significant human potential working in universities is a necessary premise to achieve greater development in the educational field. The post-pandemic impact of COVID-19, it is necessary to contextualize the organizational culture to the current times in the university institutions, prioritize academic with social projection in order to strengthen the institutional mission using more technologies with greater presence in digital platforms and positioning educational content